2023
DOI: 10.3389/fmicb.2023.1138864
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functions of stress granules in viral infection at a glance

Abstract: Stress granules (SGs) are distinct RNA granules induced by various stresses, which are evolutionarily conserved across species. In general, SGs act as a conservative and essential self-protection mechanism during stress responses. Viruses have a long evolutionary history and viral infections can trigger a series of cellular stress responses, which may interact with SG formation. Targeting SGs is believed as one of the critical and conservative measures for viruses to tackle the inhibition of host cells. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…In contrast, Chemotherapy drugs like selenite or UV exposure led to the formation of noncanonical SGs, which are less dynamic and pro-apoptotic to cells 15 , 16 . Although the concept of stress-specific SG subtypes is emerging 7 , 15 , 17 19 , their different protein and RNA compositions and functions are largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Chemotherapy drugs like selenite or UV exposure led to the formation of noncanonical SGs, which are less dynamic and pro-apoptotic to cells 15 , 16 . Although the concept of stress-specific SG subtypes is emerging 7 , 15 , 17 19 , their different protein and RNA compositions and functions are largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of SGs is an integral part of the innate immune response to viral infection 7 . All viruses require the translation machinery of the host cell to synthesize viral proteins 5 , 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, viruses dampen innate immune signaling by interfering with distinct steps in the cellular signaling cascades. A common target of viruses is to disrupt the formation of stress granules which have been implicated as signaling hubs for antiviral signaling (Guan et al, 2023 ; Lloyd, 2013 ; McCormick and Khaperskyy, 2017 ; Miller, 2011 ). Stress granules, large membrane-less protein-RNA assemblies, form in the cytoplasm in response to various stress signals, including viral infections (Protter and Parker, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous studies have demonstrated that EV71-2A pro is capable of manipulating host cell gene expression through the cleavage of various proteins, such as eIF4GI, eIF4GII, PABP, and P-body ( 6 , 21 , 22 ). In response to antiviral cellular immune defense, host cells accumulate a significant number of proteins and RNAs in the cytoplasm, resulting in the formation of envelope-free emergency granules known as stress granules (SGs) ( 23 ). The interaction between eIF4GI-RasGAP SH3 domain binding protein plays a crucial role in the conversion of typical stress granules (tSGs) into atypical stress granules (aSGs), thereby facilitating the infection caused by EV71 ( 21 , 24 ).…”
Section: Introductionmentioning
confidence: 99%